(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2024)
The rapid development of tourism affects the quality of tourist attractions in several tourist destinations, including villages that are transforming into tourist villages. With the increasing increase of tourism operations in rural areas, the quality of life in tourist villages needs to be assessed to not exceed its carrying capacity. Only when the issue becomes worse have attempts been made to address excessive tourism thus far. Slums arise in rural locations, particularly in tourist communities, as a result of one of the quality reductions. By comparing the slum criteria with input from resource people in tourist villages regarding factors reducing carrying capacity in tourist villages, this study examines factors that may be threshold aspects for developing a village so that it does not become a village that exceeds its carrying capacity. There were three phases to this study’s first review. The initial stage is a review of the literature to identify the causes of the decline in tourist communities. Secondly, an Analytic Hierarchy Process (AHP) technique survey of influential people in rural tourism was conducted to gather information for threshold-determining criteria. The last step involves comparing the rural slum parameters with the AHP results. Using the characteristics of rural slums, the comparison aims to generate an assessment of the threshold instrument for the development of tourism activities in rural regions. According to preliminary research, the slum criterion is an indicator that, when modified, could enhance the threshold instrument for building tourist villages.